Review of the spider genus Solenysa Simon, 1894 in Western Japan and Central Ryukyu with the description of three new species (Araneae, Linyphiidae) - Francesco Ballarin; Hauchuan Liao; Zento Touyama; Katsuyuki Eguchi (ZooKeys)
Three new species of the genus Solenysa Simon, 1894 are recorded and described from Western Japan, all based on both sexes. Of these, two species are endemic to the Ryukyu Archipelago: S. shimatchu Ballarin & Eguchi, sp. nov. from Amami-Ōshima Island, and S. yambaruensis Ballarin & Eguchi, sp. nov. from Okinawa Honto and Kume-jima Islands. These species represent the first record of the genus Solenysa for the Central Ryukyus and belong to a newly defined species group. Another new species, S. bilamellata Ballarin & Eguchi, sp. nov. is recorded from eastern Kyushu in mainland Japan and belongs to the mellotteei group. The phylogenetic positions of the new species are discussed based on morphological and molecular data. New records, remarks, and photos of genitalia of other poorly known Solenysa species from surrounding areas (Taiwan, Kyushu, Shikoku, and western Honshu) are provided to facilitate future identifications.